A TAHSIN-BASED PEDAGOGICAL FRAMEWORK FOR ENHANCING PHONETIC ACCURACY IN QUR’ANIC RECITATION: A QUALITATIVE STUDY AT MA’HAD AL-JAMI’AH UIN RADEN INTAN LAMPUNG - Alifia Karomatus Syifa; Wan Jamaluddin Z; Uswatun Hasanah (ASIAN PUBLISHER, 2025)
This study aims to provide a comprehensive description of the implementation of the tahsin program in enhancing Qur’anic reading proficiency at Ma’had Al-Jami’ah, UIN Raden Intan Lampung. It focuses on the pedagogical framework of the tahsin learning process, which is conducted in halaqah sessions held after the dawn prayer (ba’da Subuh), after the sunset prayer (ba’da Maghrib), and during evening classes. The research employed a descriptive qualitative approach, with the research population encompassing all tahsin activities conducted within the Ma’had. The sample was purposively selected and consisted of tahsin instructors (muallimah), the qirā’ah–tahfidz coordinator, Ma’had administrators, and active student participants. The research instruments included observation guidelines, interview protocols, and documentation sheets. Data were collected through direct observation of instructional procedures, in-depth interviews regarding coaching methods, and documentation such as activity photos and assessment archives to strengthen the findings. The results indicate that the primary method employed is the Yanbu’a approach, structured progressively from letter recognition to reading fluency, and reinforced with the talaqqi–musyafahah method to ensure accuracy of articulation (makhraj), phonetic characteristics, and the proper application of tajwīd rules. Evaluation is conducted through multiple layers, including oral recitations, reading tests, and routine coaching for muallimah. The main challenges include heterogeneous initial abilities, regional dialect interference, and fluctuating learner motivation. These challenges are addressed through placement tests, level-based grouping, remedial guidance, and teacher training. The study concludes that the methodological integration of Yanbu’a with talaqqi–musyafahah effectively improves the Qur’anic reading quality of students, offering a pedagogical approach that is both progressive and adaptive to the diverse needs of learners.